2014
DOI: 10.12693/aphyspola.126.54
|View full text |Cite
|
Sign up to set email alerts
|

Influence of High Energy Heavy Ions on Magnetic Susceptibility of Soft Magnetic Metallic Glasses

Abstract: This contribution presents experimental data concerning the inuence of fast heavy ions on magnetic susceptibility of VITROVAC R 6025 and VITROPERM R 800 metallic glasses. Samples of magnetic ribbons were irradiated with Au, and Ta ions at 11.1 MeV/A (energy per nucleon), and U ions at 5.9 MeV/A. The irradiation uences varied from 5 × 10 10 up to 1.2 × 10 13 ions/cm 2 . Relative change of the samples' magnetic susceptibility after and before irradiation was measured and evaluated as a function of the irradiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 10 publications
(8 reference statements)
0
8
0
Order By: Relevance
“…Its final value of 0.32% is more than twice as high as the value at the fluence of 2 Â 10 12 ions cm À2 (0.15%). It should be noted that a similar effect of a sudden change was observed for the magnetic susceptibility in the A alloy irradiated with the fluence of 2 Â 10 12 ions cm À2 [10,11,36]. Based on the magnetic susceptibility measurements, it was found that the A alloy is magnetically stable up to the fluence of 2 Â 10 12 ions cm À2 .…”
Section: Structural Relaxation During the Full Heating-cooling Cyclementioning
confidence: 52%
See 1 more Smart Citation
“…Its final value of 0.32% is more than twice as high as the value at the fluence of 2 Â 10 12 ions cm À2 (0.15%). It should be noted that a similar effect of a sudden change was observed for the magnetic susceptibility in the A alloy irradiated with the fluence of 2 Â 10 12 ions cm À2 [10,11,36]. Based on the magnetic susceptibility measurements, it was found that the A alloy is magnetically stable up to the fluence of 2 Â 10 12 ions cm À2 .…”
Section: Structural Relaxation During the Full Heating-cooling Cyclementioning
confidence: 52%
“…One can speculate if saturation could occur at sufficiently high fluencies (higher than 10 13 ions cm À2 ). Such a saturation tendency has been observed in magnetic susceptibility measurements [36]. However, it is noteworthy that the available fluencies are limited by the performance of the irradiation facility.…”
Section: Structural Relaxation During the Full Heating-cooling Cyclementioning
confidence: 56%
“…Details of these experiments have been reported in (10,11). It is evident that VITROPERM ® is radiation harder against heavy ions than VITROVAC ® (direct comparison is possible especially via the data for Au ions at 11.1 MeV/A).…”
Section: Resultsmentioning
confidence: 99%
“…The first group of materials could be so-called metallic glasses, especially the softmagnetic metallic alloys. They also feature similar chemical composition [15,16] and the ion-range data are needed for radiation hardness studies of these materials against ion irradiation [17][18][19][20][21]. The second possible candidates could be steels; a large family of materials made of the same iron bulk material with different additive elements and processed by different technological treatments.…”
Section: Discussionmentioning
confidence: 99%